THE EFFECT OF FIELD TRIP METHOD TOWARD THE ENHANCEMENT OF SOCIAL INTERACTION ABILITY OF CHILDREN WITH MODERATE MENTALLY RETARDED - Amelia Rizky Idhartono; Mohammad Efendi (Department of Special Education, 2016)
The background of this study was the lack of social interaction ability of children with moderate mentally retarded fourth graders of SDLB. This study was aimed at implementing a new method to overcome social interaction problem of students with moderate mentally retarded in which the method was field trip. This study employed experimental design with Single Subject Research (SSR) method. The students’ social interaction ability in percentage was 44% to 40% in baseline and 70% to 89% in intervention. 14 to 12 for the form of frequency in baseline and 31 to 37 in intervention. The overlap percentage was 0%. Thus, field trip method had a positive effect toward the social interaction ability of children with moderate mentally retarded.